Optimized hydrolytic methods by response surface methodology to accurately estimate the phenols in cereal by HPLC-DAD: The case of millet. (15th January 2020) - Balli, Diletta; Bellumori, Maria; Orlandini, Serena; Cecchi, Lorenzo; Mani, Elisa; Pieraccini, Giuseppe; Mulinacci, Nadia; Innocenti, Marzia
Highlights: Methyl ferulate was identified for the first time in the phenolic fraction of millet. Response Surface Methodology (RSM) applied for basic and acidic hydrolyses. Acidic hydrolysis gave the best yields of extracted flavonoids and phenolic acids. Total free and bound phenols were obtained in a single extractive step. Abstract: Extraction of free and bound phenols from millet in acidic and basic hydrolytic conditions were compared for the first time. Acidic hydrolysis was able to extract the highest amount of total phenolic compounds (up to 178 mg/100 g) while the basic hydrolysis underestimates the phenolic concentration. Our findings pointed out for the first time that methyl ferulate is naturally present as bound phenol in millet. Response Surface Methodology was then applied to both acidic and basic hydrolytic extractive conditions: the acidic procedure, optimized in terms of extractive time and temperature and concentration of the acidic mean, gave the best results, allowing definition of Method Operable Design Region and quantitation of the total amount of phenols in millet samples in a single extractive step. This optimized method is suitable for further accurate investigations of the typical phenols of the numerous varieties of this recently re-discovered minor cereal.